Fighting for Their Lives : Inside the Experience of Capital Defense Attorneys - Sheffer, Susannah, 1964- (Book collections on Project MUSE., 2013)
How do attorneys who represent clients facing the death penalty cope with the stress and trauma of their work? Through conversations with twenty of the most experienced and dedicated post-conviction capital defenders in the United States, this book explores this emotional territory. What it is like for these capital defenders in their last visits or phone calls with clients who are about to be taken to the execution chamber? Or the next mornings, in their lives with their families, in their dreams and flashbacks and moments alone in the car? What is it like to do this work year after year? (The attorneys interviewed for this book had, on average, spent nineteen years doing capital defense.) Through vivid interviews amplified by the author's responses and commentary, these attorneys reveal aspects of their internal experience, and provide answers to a pressing question: How do capital defenders manage the weight of the responsibility they carry?